Electrochemical Detection of Bisphenol S Based on Molecularly Imprinted Polymers Grafted on Functionalized Multiwalled Carbon Nanotubes: A Facile Sensor Fabrication Approach - Christopher Mwanza; Lin Zhao; Qing Zhang; Shou-Nian Ding (Chemosensors, 2025)
Bisphenol S (BPS), a key ingredient in polycarbonate plastics and epoxy resins, is a known endocrine-disrupting compound that poses significant risks to human health and the environment. As such, the development of rapid and reliable analytical techniques for its detection is essential. In this work, we present a newly engineered electrochemical sensor designed for the sensitive and selective detection of BPS using a straightforward and effective fabrication approach. The sensor was constructed by grafting molecularly imprinted polymers (MIPs) onto vinyl-functionalized multiwalled carbon nanotubes (f-MWCNTs). Ethylene glycol dimethacrylate and acrylamide were used as the cross-linker and functional monomer, respectively, in the synthesis of the MIP layer. The resulting MIP@f-MWCNT nanocomposite was characterized using Fourier-transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). The MIP@f-MWCNT material was then combined with chitosan, a biocompatible binder, to fabricate the final MIP@f-MWCNT/chitosan-modified glassy carbon electrode (GCE). Electrochemical evaluation showed a broad linear detection range from 1 to 60 µM (R2 = 0.992), with a sensitivity of 0.108 µA/µM and a detection limit of 2.00 µM. The sensor retained 96.0% of its response after four weeks and exhibited high selectivity against structural analogues. In spiked plastic extract samples, recoveries ranged from 95.6% to 105.0%. This robust, cost-effective, and scalable sensing platform holds strong potential for environmental monitoring, food safety applications, and real-time electrochemical detection of endocrine-disrupting compounds like BPS.